Preparation method and application of CoNiNOC diatomic electrocatalyst for electro-Fenton system
By using the CoNiNOC diatomic electrocatalyst prepared by the ZIF precursor, the problem of difficulty in effectively degrading antibiotics in wastewater in the prior art is solved, and an efficient, stable and environmentally friendly electrofenton degradation effect is achieved.
Patent Information
- Application Number
- CN202510083846.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively degrade antibiotics in wastewater, and the catalyst materials of electrofenton technology have problems such as high operating costs, complex processes, or possible toxic by-products.
The CoNiNOC diatomic electrocatalyst with ZIF as the precursor and after thermal reduction, pickling and oxidation treatment is used as a catalyst in the electrofenton system, and antibiotics are degraded in the electrofenton system through electrochemical methods.
It has achieved efficient degradation of antibiotics in wastewater, with excellent oxygen reduction performance, stability and environmental friendliness, low energy consumption, simple operation, and can effectively degrade a variety of antibiotics.
Smart Images

Figure CN119869591A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of materials and environment, and in particular to a CoNiNOC diatomic electrocatalyst for an electro-Fenton system and a preparation method thereof, as well as application of the catalyst in degrading antibiotics in wastewater. Background Art
[0002] Since the advent of penicillin in the last century, antibiotics have been widely used in human health, animal husbandry, agriculture and other fields. Their usage has continued to increase with global economic development and population growth. Antibiotics cannot be completely absorbed by humans or animals after use. A large part of them will be excreted in urine or feces in the form of original drugs or metabolites. These antibiotics migrate and enrich with water bodies, and seriously affect human health through the food chain. Over time, they may even cause adverse effects such as deformities and gene mutations.
[0003] Common antibiotic treatment technologies, such as membrane filtration, adsorption, oxidation and biological treatment, are limited in practical application due to their high operating costs, complex processes or the possibility of producing more toxic byproducts. In recent years, electro-Fenton technology has been considered one of the most promising pollutant treatment technologies due to its green and easy operation. The core of electro-Fenton technology is the synthesis of electro-Fenton catalysts, so it is urgent to prepare an electro-Fenton catalyst with high pollutant degradation efficiency, green recyclability and high economic benefits.
[0004] The present invention prepares a CoNiNOC nanocatalyst material using ZIF as a precursor, after thermal reduction, acid washing and oxidation. The electro-Fenton system is simple to operate, has low energy consumption and stable performance. The transition metal-doped carbon material catalyst has high selectivity in the process of electrocatalytic reduction of oxygen to produce hydrogen peroxide, and can catalyze hydrogen peroxide to generate hydroxyl radicals, which can effectively degrade antibiotics. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide an oxygen-doped diatomic catalyst (CoNiNOC) with multiple active sites, excellent oxygen reduction performance, strong stability, superior electro-Fenton catalytic degradation performance, and environmental friendliness, which is used as an electro-Fenton catalyst material for the degradation of antibiotics in wastewater.
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a CoNiNOC catalyst for degradation of antibiotics in an electro-Fenton system, comprising the following steps:
[0007] S1, cobalt nitrate hexahydrate (Co(NO3)2·6H2O), nickel acetylacetonate dihydrate (C 10 H 16NiO5) and zinc nitrate hexahydrate (Zn(NO3)2·6H2O) were added to a methanol solution, recorded as solution A, and dimethylimidazole was dissolved in a methanol solution, recorded as solution B. The two were mixed and stirred for 6 hours, and then allowed to stand for 12 hours to remove the supernatant. The mixture was centrifuged at 10000 rpm and washed three times with methanol, and then dried in vacuum at 60°C overnight to obtain a cobalt nickel zinc zeolite imidazoline framework (CoNiZn-ZIFs) precursor powder.
[0008] S2. Put the precursor CoNiZn-ZIFs precursor powder prepared in step S1 into an ark, place it in a tube furnace and heat it under a H2 / Ar atmosphere to obtain a cobalt-nickel double single atom (CoNiNC) material.
[0009] S3. Add the CoNiNC material obtained in step S2 to an appropriate volume of HNO3 solution, heat and stir at 80°C for 48h, and finally obtain oxygen-doped cobalt-nickel double single atom (CoNiNOC) material after centrifugation, washing and drying.
[0010] In one embodiment of the present invention, the molar ratio of the cobalt nitrate hexahydrate, nickel acetylacetonate dihydrate, zinc nitrate hexahydrate, and dimethylimidazole in step S1 is 1:1:3:11.
[0011] In one embodiment of the present invention, the amount of methanol used in step S1 is 50-80 mL.
[0012] In one embodiment of the present invention, the atmosphere of the tube furnace described in step S2 is a 5% H2 / Ar mixed gas.
[0013] In one embodiment of the present invention, the temperature program of the tube furnace in step S2 is: first heating to 800°C, keeping warm for 1 hour, then heating to 900°C, keeping warm for 1 hour, then heating to 1000°C, keeping warm for 1 hour. Finally, the temperature is increased to 10°C / min. -1 The temperature was cooled to 300 °C at a rate of 5 °C min-1 and then cooled to room temperature naturally. -1 .
[0014] In one embodiment of the present invention, the volume of the HNO3 solution in step S3 is 10 to 20 mL.
[0015] The invention also provides a CoNiNOC nano catalyst prepared according to the method.
[0016] In addition, the present invention also provides application of the catalyst in wastewater degradation.
[0017] Furthermore, the application includes degradation of tetracycline, ofloxacin (Ofloxacin, OFL), sulfadiazine (Sulfadiazine, SDZ) and amoxicillin (Amoxicillin, AMX) in wastewater.
[0018] The method for degrading antibiotics in wastewater using a CoNiNOC catalyst provided by the present invention comprises the following steps: using carbon paper loaded with a catalyst as a cathode, a platinum sheet as an anode, placing a cathode and an anode in parallel in an electrolytic cell, adding a mixed solution of an electrolyte and wastewater into the electrolytic cell, connecting the other ends of the cathode and the anode to corresponding electrodes of a direct current power supply, continuously introducing oxygen into the solution, and continuously stirring.
[0019] Wherein, the electrolyte is perchloric acid, the concentration of the electrolyte solution is 0.1 mol / L, the pH of the electrolyte solution is 1.0, the degradation of antibiotics in the wastewater is carried out by chronoamperometry at a potential of 0.15 V vs. RHE; the concentration of antibiotics in the mixed solution is 20 mg / L; and the electrolysis time is 120 min.
[0020] In the present invention, the principle of the electro-Fenton degradation method of antibiotics in aqueous solution is: under the output conditions of the chronoamperometry principle, the introduced oxygen undergoes double electron transfer under the cathode to generate H2O2 in situ. Then, H2O2 contacts and reacts with the active sites on the catalyst surface to generate hydroxyl radicals (·OH), which effectively promotes the degradation and mineralization of antibiotics.
[0021] Compared with the prior art solutions, the advantages and effects of the present invention are:
[0022] (1) Ni sites were introduced to prepare CoNiZnZIFs precursors and subjected to temperature gradient pyrolysis and nitric acid pickling to synthesize oxygen-doped diatomic CoNiNOC electrocatalysts. SEM, XRD and HRTEM tests proved that CoNiNOC was an oxygen-doped diatomic material. ICP-MS and XPS tests proved that the introduction of Ni sites increased the loading of metal active sites. XPS revealed that the oxygen-containing functional groups in CoNiNOC were mainly COC groups.
[0023] (2) Electrochemical tests have proven that CoNiNOC has excellent 2e - ORR activity and selectivity, with a ring current density close to 3.0 mA cm -2 The highest hydrogen peroxide selectivity reached 96%, and a high selectivity of more than 90% can be achieved in a wide potential range. The KSCN poisoning experiment proved that the active site in CoNiNOC is a metal diatomic site. The COC group changes the electronic structure of the metal diatomic site, inhibits the breaking of the OO bond, and thus improves the 2e- The selectivity of ORR. After 100 hours of stability testing, the current density did not show obvious attenuation, and the average H2O2 yield was 1.54 mol g catalyst -1 h -1 , the highest FE exceeds 90%.
[0024] (3) TC degradation was carried out on the CoNiNOC electro-Fenton cathode, achieving a TC degradation rate of 96.0% in 120 min, a TOC degradation rate of 90.0% in 180 min, and a TOC degradation rate of 0.024 min. -1 The high kinetic rate constant of CoNiNOC cathode was obtained. In addition, the TC degradation rate can still be maintained at more than 93% after 6 cycles, showing excellent cyclic stability. The electro-Fenton degradation experiment after free radical capture confirmed the key role of OH radicals in the electro-Fenton process. Finally, the electro-Fenton degradation of multiple antibiotics proved the universality of CoNiNOC cathode electro-Fenton system in degrading difficult-to-degrade antibiotic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the H-cell device for degradation of antibiotics by the electro-Fenton method of the present invention;
[0026] Figure 2 The synthesis flow chart of the CoNiNOC catalyst in the present invention;
[0027] Figure 3 The SEM images and magnified images of the CoNiZnZIFs precursor, CoNiNC, and CoNiNOC in the present invention;
[0028] Figure 4 TEM images of CoNiZnZIFs precursor, CoNiNC and CoNiNOC in the present invention;
[0029] Figure 5 EDS images of CoNiZnZIFs precursor, CoNiNC and CoNiNOC in the present invention;
[0030] Figure 6 is the X-ray diffraction spectrum of CoNiNOC and CoNiNC in the present invention;
[0031] Figure 7 is the Raman spectra of CoNiNOC and CoNiNC in the present invention;
[0032] Figure 8 is the Fourier transform infrared spectrum of CoNiNOC and CoNiNC in the present invention;
[0033] Fig. 9TC degradation efficiency curve of CoNiNOC and CoNiNC in the electro-Fenton system of the present invention;
[0034] Fig.10 The electro-Fenton TC degradation efficiency curves of the present invention when different free radical scavengers are added and when no scavenger is added;
[0035] Fig.11 The degradation efficiency curves of the four antibiotics, sulfadiazine, ofloxacin, tetracycline and amoxicillin, in the CoNiNOC cathode electro-Fenton system of the present invention;
[0036] Fig.12 : TOC degradation efficiency curves of sulfadiazine, ofloxacin, tetracycline and amoxicillin in the CoNiNOC cathode electro-Fenton system of the present invention. DETAILED DESCRIPTION
[0037] The present invention will be further described below by way of examples, but the embodiments of the present invention are not limited thereto.
[0038] Example 1
[0039] The synthesis steps of CoNiNOC catalyst are as follows:
[0040] (1) 0.5 g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 0.47 g of nickel acetylacetonate dihydrate (C 10 H 16 NiO5), 2g zinc nitrate hexahydrate (Zn(NO3)2·6H2O) was dissolved in 50mL methanol solution as solution A, and 2.5g dimethylimidazole was dissolved in 80mL methanol solution as solution B. Solution B was injected into solution A while stirring vigorously, and stirring was continued for 6 hours, and then aged for 12 hours to remove the supernatant. The precipitate was collected by centrifugation at 10000rpm and washed three times with methanol. Finally, it was vacuum dried at 60°C overnight to obtain the cobalt nickel zinc zeolite imidazoline framework (CoNiZn-ZIFs) precursor powder.
[0041] (2) The CoNiZn-ZIFs precursor powder was collected into a ceramic ark and placed in the center of a tube furnace. -1 The temperature was raised to 800°C at a rate of 100°C and kept at that temperature for one hour. Then, the temperature was raised to 900°C at the same rate and kept at that temperature for one hour. Finally, the temperature was raised to 1000°C and kept at that temperature for one hour. Then, the temperature was raised to 1000°C at a rate of 10°C min. -1 The material was cooled to 300°C at a cooling rate of 100°C and then naturally cooled to room temperature to obtain cobalt-nickel double single atom (CoNiNC) material.
[0042] (3) Dissolve the CoNiNC powder in a certain volume of 2M HNO3 solution and ultrasonicate for 10 minutes until a uniform suspension is formed. Then heat and stir the solution at 80°C for 48 hours to modify the oxygen-containing functional groups. After centrifugation, washing, and drying, oxygen-doped cobalt nickel double single atom (CoNiNOC) material is obtained.
[0043] Comparative Example 1
[0044] The difference between Comparative Example 1 and Example 1 is that step (3) is omitted.
[0045] The morphology, structure and element distribution of the CoNiNOC synthesized in Example 1 and the CoNiNC synthesized in Comparative Example 1 were characterized by SEM, TEM and EDS. Figure 3 and 4 As shown, CoNiNOC and CoNiNC basically retain the typical rhombic dodecahedral structure of the original CoNiZn-ZIFs, indicating that annealing and pickling treatments do not significantly affect the morphology of the material. The particle size of these dodecahedral structures is 100-200nm; SEM, HRTEM and HAADF-STEM images of CoNiNOC materials are shown, showing that CoNiNOC materials are dodecahedral structures. No Co nanoparticles were observed in the high-resolution transmission electron microscopy images, and the lattice fringes of the (002) crystal plane of graphitized carbon were not obvious, indicating that the introduction of Ni sites and the change of annealing atmosphere significantly reduced the degree of graphitization of the material.
[0046] XRD is used to analyze the crystal information of the material. Figure 6 The XRD spectra of CoNiNOC and CoNiNC are shown in Figure 2. The diffraction peaks corresponding to the (111), (200), (220) crystal planes of metal Co and the (111), (200), (220) crystal planes of metal Ni are not observed in the XRD curves of the two samples, indicating that there are no metal Co and Ni particles in the sample after high-temperature decomposition of CoNiZnZIFs. This proves that the introduction of Ni sites increases the spacing between Co single-atom sites and promotes the isolation and distribution of CoNi sites, thereby forming a CoNi double single-atom structure. On the other hand, the CoNiNOC and CoNiNC samples have similar XRD curves. The two diffraction peaks observed at 26° and 44° correspond to the (002) and (101) crystal planes of amorphous carbon, respectively, and the diffraction peaks are wide and large, indicating that the material is mainly an amorphous carbon structure. Corresponding to the TEM spectrum in the previous article, it further shows that the introduction of Ni sites and the change of annealing atmosphere greatly reduce the degree of graphitization of the material.
[0047] Raman spectra of the pyrolyzed samples, such as Figure 7 As shown, shown at 1330 and 1580cm -1There are two peaks at , corresponding to the D band representing defective carbon and the G band related to graphitized carbon. D / I G The values are all higher, further proving the lower graphitization degree of the material. On the other hand, compared with CoNiNC, the I D / I G The higher the value, the more defective carbon there is, which indicates that oxygen doping helps to increase the defective carbon content in the material, thereby improving 2e - Activity and selectivity of ORR.
[0048] FTIR is used to observe the functional group information of the sample. Figure 8 As shown, CoNiNOC at 3410 cm -1 A stronger hydroxyl stretching vibration peak appeared at 1581 cm -1 and 1213cm -1 At the same time, there are stronger peaks corresponding to C=C and CO functional groups at 1716cm -1 The absorption band of C=O bond appears at , indicating that a large number of oxygen-containing functional groups are introduced into the CoNiNOC sample after nitric acid washing.
[0049] Example 2
[0050] Application of CoNiNOC in heterogeneous electro-Fenton system
[0051] First, the CoNiNOC catalysts synthesized in Example 1 and the CoNiNC catalysts synthesized in Comparative Example 1 were prepared into electro-Fenton cathodes, and electro-Fenton degradation of tetracycline was tested in a single-chamber electrolytic cell. Fig. 9 As shown, at pH = 3 and Fe 2+ Under the condition of 0.5mM concentration, after 120min of Fenton degradation experiment, the degradation efficiency of tetracycline can reach 96%, which is much higher than 40% of CoNiNC. This shows that the presence of oxygen doping makes the 2e - The ORR activity and selectivity are enhanced, and more hydrogen peroxide is produced at the electro-Fenton cathode, which promotes the electro-Fenton reaction. In order to reduce the various toxic intermediates produced when tetracycline mineralization is incomplete during the advanced oxidation process, we need to convert as much tetracycline as possible into non-polluting CO2 and H2O.
[0052] In the electro-Fenton process, pollutants are mainly transported through Fe 2+The free radicals generated by the reaction with H2O2 were subjected to in-situ oxidative degradation. In order to determine which of the two free radicals plays a decisive role in the electro-Fenton system, the two free radicals were captured in the electrolyte by different scavengers (TBA captures hydroxyl radicals and BQ captures superoxide radicals), and then the electro-Fenton degradation test was carried out, such as Fig.10 As shown. After TBA captured hydroxyl radicals, the TC degradation rate was 50% at 120 min, which was much lower than 96% without adding capture agent and 80% after BQ captured superoxide radicals. The electro-Fenton performance decreased most significantly after capturing hydroxyl radicals, indicating that ·OH radicals play a major role in the electro-Fenton process, which is consistent with a large number of studies.
[0053] In order to prove the universality of the CoNiNOC electro-Fenton system in degrading organic pollutants such as antibiotics, four antibiotics, ofloxacin, amoxicillin, sulfadiazine and tetracycline, were selected for electro-Fenton degradation tests. Fig.11 It can be seen that after 120 min of electro-Fenton degradation test, the four antibiotics, amoxicillin (97.1%), tetracycline (96.0%), ofloxacin (90.0%), and sulfadiazine (83.4%), all have high degradation efficiency.
[0054] The electro-Fenton degradation time was extended and the TOC degradation rate after 180 min was tested. The results are as follows Fig.12 As shown. The TOC degradation efficiencies of four antibiotics, amoxicillin, tetracycline, ofloxacin and sulfadiazine, were 92.61%, 90.21%, 86.57% and 81.36%, respectively, and most antibiotics were eventually degraded into non-polluting substances such as carbon dioxide, water and inorganic ions. These results indicate that the prepared CoNiNOC electro-Fenton cathode is a promising electro-Fenton cathode material that can remove organic pollutants such as a variety of antibiotics.
[0055] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a CoNiNOC diatomic electrocatalyst for an electro-Fenton system, characterized in that: The following steps are involved: S1: dissolving cobalt nitrate hexahydrate, nickel acetylacetonate dihydrate, and zinc nitrate hexahydrate in a methanol solution as solution A, and dissolving dimethylimidazole in a methanol solution as solution B, and then mixing and stirring the solution A and solution B evenly, standing to remove the supernatant, centrifuging and washing with methanol, and then vacuum drying to obtain CoNiZn-ZIFs precursor powder; S2: putting the CoNiZn-ZIFs precursor powder in step S1 into an ark, placing it in a tube furnace and heating it under a H2 / Ar atmosphere to obtain a CoNiNC material; S3: Add the CoNiNC described in step S2 into a nitric acid solution, heat and stir, centrifuge, wash, and dry to obtain a CoNiNOC catalyst.
2. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of the cobalt nitrate hexahydrate: nickel acetylacetonate dihydrate: zinc nitrate hexahydrate: dimethylimidazole is 1:1:3:
11.
3. The preparation method according to claim 1, characterized in that: In step S1, the amount of methanol used is 50-80 mL.
4. The preparation method according to claim 1, characterized in that: In step S2, the atmosphere of the tubular furnace is a 5% H2 / Ar mixed gas.
5. The preparation method according to claim 1, characterized in that: In step S2, the heating temperature program is: first heating to 800°C, keeping the temperature for 1 hour, then heating to 900°C, keeping the temperature for 1 hour, then heating to 1000°C, keeping the temperature for 1 hour, and then heating at 10°C·min -1 The sample was cooled to 300 °C at a cooling rate and then naturally cooled to room temperature.
6. The preparation method according to claim 5, characterized in that: The heating rate during heating was 5℃·min -1 .
7. The preparation method according to claim 1, characterized in that: The volume of the nitric acid solution described in step S3 is 10-20 mL.
8. Use of the CoNiNOC catalyst prepared by the method according to any one of claims 1 to 7 in electro-Fenton degradation of antibiotics in wastewater.
9. The use according to claim 8, characterized in that: The applications include degradation of antibiotics in wastewater, including tetracycline, ofloxacin, sulfadiazine and amoxicillin.
10. The operating method of the application according to any one of claims 8 to 9, characterized in that: The method for degrading antibiotics in wastewater using CoNiNOC catalyst comprises the following steps: using carbon paper loaded with CoNiNOC as a cathode, a platinum sheet as an anode, placing the cathode and cathode in parallel in an electrolytic cell, adding a mixed solution of electrolyte and wastewater into the electrolytic cell, connecting the other ends of the cathode and cathode to corresponding electrodes of a DC power supply, continuously introducing oxygen into the solution, and continuously stirring; The concentration of the electrolyte in the mixed solution is 0.1 mol / L, and the pH of the electrolyte solution is 1.0; The degradation of antibiotics in wastewater was carried out using chronoamperometry at a potential of 0.15 V vs. RHE; The concentration of antibiotics in the mixed solution is 20 mg / L; The electrolysis time is 120 min.
Citation Information
Patent Citations
Carbon nitride-loaded bimetallic monatomic catalyst as well as preparation method and application thereof
CN115400775A
Preparation method and application of CoNiFe-MOF / LDH catalyst for electro-Fenton system
CN117619444A
Nickel-cobalt oxide Fenton-like catalyst as well as preparation method and application thereof
CN118698550A
Toc degradation in wastewater using transition metal catalysts
WO2009013313A1
Cited By
Catalyst for packaging rare alloy nanoparticles as well as preparation method and application of catalyst
CN117399012A
A catalyst encapsulating rare alloy nanoparticles, and a preparation method and application thereof
CN117399012B